3D-printed glass microfluidics for fluid dynamics and rheology. (October 2019) - Burshtein, Noa; Chan, San To; Toda-Peters, Kazumi; Shen, Amy Q.; Haward, Simon J.
Abstract: Microfluidics provides a versatile platform for handling small volumes of fluids at small length scales. From a fluid dynamics perspective, microfluidics gives access to a regime of very high deformation rates γ ˙ at moderate to negligible Reynolds numbers R e . For viscoelastic fluid flows, the resulting high Weissenberg numbers W i = τ γ ˙, where τ is the fluid characteristic time, means the flow occurs at high elasticity number E l = W i / R e . Consequently, microfluidics supports a burgeoning interest in the experimental study of purely elastic flow instabilities and elastic turbulence. However, for rheological studies, typical microfluidic fabrications by soft lithography in poly (dimethyl siloxane) suffer from a number of limitations arising from the low elastic modulus and poor optical properties of the material. In this review, we summarise a few recent studies from our group in which we have experimented with microdevice fabrications using the subtractive three-dimensional (3D)-printing technique of selective laser-induced etching (SLE). SLE can be used to fabricate arbitrary 3D geometries with micron precision in fused silica: a high modulus, highly transparent material, which is robust and resistant to organic solvents. Apart from high elasticity number flows, we have found that SLE fabricated devices can sustain very high deformation rates without device failure, providing new access to little-explored inertio-elastic regimes in extremely dilute polymer solutions. Furthermore, it is possible to visualize flows from multiple planes of observation, allowing the quantitative study of 3D flow instabilities and vortex dynamics in both Newtonian and non-Newtonian fluids. SLE fabrication offers many new opportunities to those involved in fluid dynamics and rheology research at the microscale, and we highlight what we perceive as potentially fruitful ideas for future studies using this technique. Graphical abstract: Image 1